Pre-Service Elementary Teachers’ Perceptions of Sustainable Development Goals (SDGs)-Oriented Learning - Bramianto Setiawan; Farid Ahmadi; Sarwi Sarwi (Universitas Negeri Semarang, 2026)
This study investigates pre-service elementary teachers’ perceptions of Sustainable Development Goals (SDGs)-oriented learning by examining four key dimensions: relevance, pedagogical value, feasibility, and readiness. Employing a quantitative descriptive survey design, the study involved 75 students enrolled in the Elementary School Teacher Education (PGSD) program at a higher education institution located in Bekasi Regency, Indonesia. Data were collected through a validated questionnaire using a five-point Likert scale and analyzed through descriptive statistics, complemented by inferential analysis using Welch’s independent-samples t-test and effect size estimation. The findings reveal that pre-service elementary teachers perceive SDGs-oriented learning as highly relevant to elementary education goals and as having strong pedagogical value, particularly in promoting meaningful, contextualized, and interdisciplinary learning experiences. However, perceptions related to feasibility and readiness were comparatively moderate. Participants expressed concerns regarding curriculum integration, availability of instructional resources, and confidence in designing and implementing SDGs-oriented learning activities. Despite these challenges, respondents demonstrated high willingness to apply SDGs-oriented learning in their future classrooms and strong interest in receiving further professional training. Inferential analysis indicated no statistically significant differences in perceptions based on gender, and effect size analysis confirmed that observed differences were minimal in practical terms. Overall, the results suggest a clear gap between conceptual acceptance and practical preparedness among pre-service elementary teachers. These findings highlight the need for teacher education programs to strengthen practice-oriented approaches, including concrete instructional models and experiential learning opportunities, to enhance readiness for effective SDGs integration in elementary education.